Penggunaan Quantitative Strategic Planning Matrix (QSPM) untuk Menentukan Strategi Pemasaran Produk Air Minum Dalam Kemasan di PT. X - Andi Velahyati; Riskawati; Maghfirah Nursinta Taha (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
Marketing strategy is a policy implemented by a company to win competition within an industry. By determining the right marketing strategy, a company can achieve a competitive advantage over its rivals. PT. X is a producer of bottled drinking water (AMDK) in South Sulawesi. PT. X aims to determine an effective marketing strategy for their company to compete with other brands and increase profitability. This research utilizes the Quantitative Strategic Planning Matrix (QSPM) to determine which strategic alternative is the most attractive or appropriate for PT. X, based on the analysis of influencing external and internal factors. The data source used consists of respondent answers from questionnaires distributed to the marketing manager of PT. X. The data analysis technique follows the analytical steps of the QSPM to select strategic alternatives. The results indicate that the strategic alternative for marketing PT. X's bottled water products is to enhance and expand sales access through social media, with a Total Attractiveness Score (TAS) of 0.789